2010
DOI: 10.1186/1471-2458-10-15
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose testing and primary prevention of diabetes mellitus type 2 - evaluation of the effect of evidence based patient information

Abstract: BackgroundEvidence-based patient information (EBPI) has been recognised as important tool for informed choice in particular in the matter of preventive options. An objective, on the best scientific evidence-based consumer information about subthreshold elevated blood glucose levels (impaired fasting glucose and impaired glucose tolerance) and primary prevention of diabetes, is not available yet. Thus we developed a web-based EBPI and aim to evaluate its effects on informed decision making in people 50 years or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Thus, biological functioning in middle and later adulthood may be particularly affected by recent SES adversity experience, but still bear the scars of SES adversity experience earlier in the life course. A number of investigations have found that associations between childhood SES and health indicators in adulthood are attenuated when accounting for adult SES, although, similar to the present findings, some investigations still find an independent association for childhood SES (e.g., Galobardes et al, 2008; Haas, 2008; Tamayo et al, 2010). …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, biological functioning in middle and later adulthood may be particularly affected by recent SES adversity experience, but still bear the scars of SES adversity experience earlier in the life course. A number of investigations have found that associations between childhood SES and health indicators in adulthood are attenuated when accounting for adult SES, although, similar to the present findings, some investigations still find an independent association for childhood SES (e.g., Galobardes et al, 2008; Haas, 2008; Tamayo et al, 2010). …”
Section: Discussionsupporting
confidence: 80%
“…This includes risk of development of infectious illness, as well as chronic health conditions, such as heart disease, diabetes, and poor cognitive and physical functioning (see Cohen, 1999; Kaplan & Keil, 1993; Strike & Steptoe, 2004; Tamayo et al, 2010). Those of lower SES are also at greater risk of disease-specific and all-cause mortality (e.g., Lynch et al, 1994; Turrell et al, 2007).…”
mentioning
confidence: 99%
“…Further variables included were knowledge before intervention (ordinal, 4 questions = 0 to 4 correct answers = 4 values), self-reported former blood glucose measurements (surveyed: yes/no), increased blood pressure (high: yes/no) and blood lipid levels (elevated: yes/no), age and gender as potential confounders [7, 10]. Demographic and socioeconomic variables of the study population were described by frequency tables and mean ± standard deviation depending on the distribution of the variables, stratified by the intervention and control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Further details can be found in the published study protocol [15] and in the Supporting Information (Appendix S1). Individuals were randomly assigned to the intervention group receiving evidence-based patient information, and the control group receiving standard information from the Internet.…”
Section: Study Design and Settingmentioning
confidence: 99%